Description of Sanitation in Traditional Markets in Atambua City - Hanmina, Matildis Yulisti; Salmun, Jhony; Doke, Soni (Timorese Journal of Public Health, 2021)
The market is one of the public places that need attention to environmental sanitation. This is because traditional markets in Indonesia are synonymous with dirty, smelly, muddy, stuffy places and become breeding grounds for disease-transmitting animals such as cockroaches, mice, flies and mosquitoes which can eventually transmit disease. The sanitation conditions of Pasar Baru and Pasar Lolowa generally have a dirty market environment, poor waste management system, smelly toilets and no hand washing facilities. This study aims to determine the description of market sanitation in traditional markets in Atambua City, Belu Regency. This type of research is quantitative with a descriptive design and a survey method approach. This research started in October-November 2021. The population in this study were all traditional markets located in Atambua, Belu Regency, while the samples of this study were Atambua Baru Market and Lolowa Market. Data were collected by means of observation and interviews with percentage analysis. The results showed that 40% of Atambua's New Market and 24% of Lolowa's Market were in a poor category according to the healthy market assessment form according to the Ministry of Health of the Republic of Indonesia in 2008. Healthy Market Sanitation for the New Market and Lolowa Market was categorized as lacking or not meeting the assessment requirements. Therefore, it is recommended to all parties, especially market managers to improve and improve market sanitation by providing trash bins, hand washing facilities, clean water facilities, closing the sewerage with lattices and dividing the existing toilets separately between men and women